Perspective: Pivotal translational hematology and therapeutic insights in chronic myeloid hematopoietic stem cell malignancies. Issue 4 (15th April 2022) - Mughal, Tariq I.; Pemmaraju, Naveen; Bejar, Rafael; Gale, Robert P.; Bose, Prithviraj; Kiladjian, Jean‐Jacques; Prchal, Josef; Royston, Daniel; Pollyea, Daniel; Valent, Peter; Brümmendorf, Tim H.; Skorski, Tomasz; et al.
Abstract: Despite much of the past 2 years being engulfed by the devastating consequences of the SAR‐CoV‐2 pandemic, significant progress, even breathtaking, occurred in the field of chronic myeloid malignancies. Some of this was show‐cased at the 15th Post‐American Society of Hematology (ASH) and the 25th John Goldman workshops on myeloproliferative neoplasms (MPN) held on 9th‐10th December 2020 and 7th‐10th October 2021, respectively. The inaugural Post‐ASH MPN workshop was set out in 2006 by John Goldman (deceased) and Tariq Mughal to answer emerging translational hematology and therapeutics of patients with these malignancies. Rather than present a resume of the discussions, this perspective focuses on some of the pivotal translational hematology and therapeutic insights in these diseases.